Physical Education Learning Accommodation for Students with Special Needs at the Elementary School Level in Rantau Pulung District - Suratno, Suratno (Journal of Management Economic and Financial, 2025)
This research aims to analyse the learning accommodations in physical education (PE) implemented for students, particularly those with special needs, at the elementary school level in Rantau Pulung District. Learning accommodations are essential approaches designed to meet the educational needs of individuals with differences and limitations, enabling them to And then there' participate in PE activities. The accommodations applied, such as modifications to equipment and teaching methods, create a more inclusive and supportive environment for all students. Teachers trained in learning accommodations have a significantly greater impact on student success. Educators who have participated in inclusive education training are better equipped to identify student needs and adapt their teaching methods accordingly. Following the implementation of appropriate accommodations, 80% of students demonstrated increased participation in PE activities, while 75% of teachers reported feeling more confident in teaching PE after attending training on accommodations for students with special needs. The methodology employed in this study is qualitative descriptive, using a case study approach that involves interviews and analysis of relevant documents. The findings reveal various forms of accommodations applied by educators, including material modifications, adjustments in teaching strategies, and the use of assistive tools that facilitate the participation of students with special needs in PE lessons. Furthermore, the involvement and support of parents and the surrounding community play a crucial role in the success of these accommodations. This research is expected to contribute to the development of inclusive education and enhance the quality of education for students with special needs in Rantau Pulung District.